Playing Lego Increase Cognitive Development on Preschool Child (4-5 Years Old) - Sri Utami; Nuzul Qur'aniati; Erlita Kusuma (Universitas Airlangga, 2008)
Introduction: The preschool cognitive development can be stimulated with playing activity. The preschool child who stimulateless, their creativity will be checked and it can effect their cognitive development. Playing lego is one of the stimulation which give chance to the preschool child to express creativity and explorate their skill in playing construction. This research was aimed to analyze the effect of playing lego to the preschool cognitive development. Method: Quasy experimental pre post test design was used in this research. Total sample were 18 preschool child (4-5 years old). The independent variable was playing lego and the dependent variable was the cognitive development. Data were analyzed by Wilcoxon Signed Rank Test and Mann Whitney U Test with the significance α<0.05. Result: Result showed that the control group has significance level p=0.059 and the treatment group has significance level p=0.008. The result of Mann Whitney U Test showed p=0.001. Discussion: It can be concluded that playing lego can effect the preschool cognitive development in spatial factor, reasoning, memory, and perceptual speed. It can be suggested to the further research to examine the effect of playing lego to the motoric development or social development.